A signal conditioning module for denoising Electrocardiogram signals (2023)
In this work, we propose to use an optimal multiband filter with least mean square algorithm to design a signal conditioning module for denoising Electrocardiogram (ECG) signals contaminated with predominant noises. The module is implemented on a Field Programmable Gate Array (FPGA) hardware. The experimental results of the proposed module are investigated and compared using an ECGID database available on Physionet. Quantitative and qualitative analysis is performed using Signal to Noise Ratio (SNR), Mean Square Error (MSE), and quality indexes to assess the effectiveness of the module. The average values of SNR are 10.90124, and MSE is 0.001761, indicating the successful elimination of noises in the filtered ECG signal using the proposed module. The signal quality indexes also demonstrate that the relevant information for diagnosing cardiac functionality is preserved. Furthermore, the performance of the designed module is tested on ECG signals obtained from electrodes placed on the human body. The Spartan 3s500efg320-5 FPGA device is employed to implement the filter design module using the partial serial architecture.